Characterization of antagonistic bacteria and induced systemic resistance in rice against Xanthomonas oryzae pv. oryzae - Azman, Noor Aisyah (2017)
Rice is one of the most important food crops and being the staple food for more than half of the world population. One of the most important rice diseases is bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae (Xoo). Biological control is globally accepted as an alternative source to chemical control which can be used as antagonist against the pathogen and also can improve plant growth. Bacteria were screened for their potential use as antagonists against Xoo. Ninety three bacteria were successfully isolated where 16 isolates had the potential as antagonistic bacteria against Xoo. All 16 antagonistic bacteria were significantly different on protease, cellulase and lipase activity; siderophore and indole acetic acid (IAA) production and phosphate solubilization activity. They also were positive on nitrogen fixation activity, resistance to Chloramphenicol at 10, 30, 50 μg/ml, and Streptomycin at 10 μg/ml; and were negative to hypersensitivity test on tobacco which indicates that they were nonpathogenic bacteria towards plant species. Molecular identification by 16s rRNA amplification successfully identified all 16 antagonistic bacteria as Bacillus licheniformis (1), Acinetobacter sp. (2), Bacillus sp. (5), Pseudomonas putida (1), Burkholderia cepacia (1), Bacillus amyloliquefaciens (1), Staphylococcus warneri (1), Pantoea vagans (1), Pantoea sp. (1), Oceanobacillus oncorhynchi (1) and Paenibacillus cineris (1). Bacillus licheniformis UPMC10 and Acinetobacter sp. JITUC7 were the most potential antagonistic bacteria against Xoo and were used as seed treatment. The percentage germination, vigor index, BLB disease severity, plant height, no. of tillers and grain weight treated plants with Bacillus licheniformis UPMC10, Acinetobacter sp. JITUC7 and combination of Bacillus licheniformis UPMC10 with Acinetobacter sp. JITUC7 were significantly different. After inoculation with Xoo, general defence (0.19 to 0.87); SA-biosynthesis (0.18 to 0.69); SA-response (0.10 to 0.59); JA-biosynthesis (0.48 to 1.10); JA-response (0.21 to 0.67); ETbiosynthesis (0.14 to 0.64) and ET-signalling (0.10 to 0.49) gene expression were higher for treatment plants compared with control. General defence (0.07 to 0.11); SAbiosynthesis (0.04 to 0.15); SA-response (0.03 to 0.10); JA-biosynthesis (0.13 to 0.43); JA-response (0.18 to 0.41); ET-biosynthesis (0.02 to 0.13) and ET-signaling (0.06 to 0.21) gene expression were recorded for control plants.